Alarming Rise of MDR Bacteria in Uremia Patients in Iraq: Peningkatan Mengkhawatirkan Bakteri MDR pada Pasien Uremia di Irak - Ahmad Shandookh Hameed (Universitas Muhammadiyah Sidoarjo, 2024)
Background: Uremia, a common complication of chronic kidney disease (CKD), compromises patient immunity and increases susceptibility to bacterial infections. Frequent hospital visits further exacerbate this vulnerability. Specific Background: In Nasiriyah City, managing infections in uremia patients is complicated by multidrug resistance (MDR) and extensively drug resistance (XDR). Knowledge Gap: Despite the critical nature of this issue, the prevalence and resistance distribution of MDR and XDR bacterial isolates in uremia patients in this region have not been extensively studied. Aims: This research aims to establish the prevalence and resistance distribution of MDR and XDR bacterial isolates from uremia patients in Nasiriyah City, with an emphasis on treatment and infection control strategies. Methods: A cross-sectional study was conducted at Al-Hussein Teaching Hospital from February 2023 to January 2024. Results: The study identified Escherichia coli (40%), Klebsiella pneumoniae (30%), Staphylococcus aureus (20%), and Pseudomonas aeruginosa (10%) as predominant pathogens. High resistance rates were observed against Ampicillin (95%), Amoxicillin-Clavulanate (80%), and Ceftriaxone (75%), Novelty: This study provides the first comprehensive data on the prevalence and resistance profiles of MDR and XDR bacterial isolates in uremia patients in Nasiriyah City. Implications: The findings highlight the urgent need for stringent infection control measures, the application of effective antibiotics like carbapenems, and the development of alternative therapeutic strategies. Highlight: High resistance to Ampicillin (95%) and Amoxicillin-Clavulanate (80%). Lowest resistance to Imipenem (5%) and Meropenem (10%). Urgent need for Antimicrobial Stewardship Programs. Keyword: Uremia, CKD, MDR bacteria, antibiotic resistance, Nasiriyah City